Terrestrial lion roars and non‐Maxwellian distribution. Issue 12 (27th December 2014) - Qureshi, M. N. S.; Nasir, Warda; Masood, W.; Yoon, P. H.; Shah, H. A.; Schwartz, S. J.
Abstract Lion roars are low‐frequency (∼100 Hz) whistler waves frequently observed in the Earth's magnetosheath. By analyzing both wave and electron data from the Cluster spacecraft, and comparing with linear Vlasov kinetic theory, Masood et al. (2006) investigated the underlying cause of the lion roar generation. However, the analysis based upon the bi‐Maxwellian distribution function did not adequately explain the observations qualitatively as well as quantitatively. This outstanding problem is revisited in the present paper, and a resolution is put forth in which, the flat‐top non‐Maxwellian distribution function with a velocity power law energetic tail, known as the (r, q) distribution, or the generalized kappa distribution is employed. Upon carrying out the linear stability analysis of the (r, q) distribution against the whistler wave perturbation, and upon comparison with the Cluster data, good qualitative and quantitative agreements are found between theory and data.